Mobilize, invent and intervene in the University context: research, prevention and intervention as actions against the pandemic COVID - 19 - Jacó-Vilela, Ana Maria; Toledo Quadros, Laura Cristina de; Carneiro da Cunha, Claudia (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2022)
This text presents the initiatives of a public University of the State of Rio de Janeiro, Brazil during the first moments of the Covid-19 pandemic. It seeks to point out how, in a brief period of time, marked by many intensities due to a new pandemic, numerous activities related to the history of the Institute of Psychology and the University that houses it were organized. As this is an experience report, it describes research, intervention and extension activities carried out by its faculty and students, analyzing the impacts of each one of them not only to the outside world but also to the inside of the institution in its continuous development process facing social demands and historical challenges. The results of this work reveal the major purpose of the University in fulfilling its social commitments and enforcing the tripod of teaching, assistance and research, benefiting the university community, but especially the disadvantaged social groups linked to it.